Intracranial subdural hematoma following spinal anesthesia: A case report and literature review - Shinn-Long Lin; Chun-Chang Yeh; Zhi-Fu Wu; Ru-Yu Pan; Wei-Cheng Tseng (Journal of Medical Sciences, 2021)
Intracranial subdural hematoma (ICSH) is a rare complication of spinal anesthesia (SA). Because of similar characteristics with postdural puncture headache (PDPH), the definitive diagnosis of ICSH is usually delayed or masked, which potentially results in morbidity or mortality. Herein, we report the case of a young male who developed ICSH following SA and emphasize the differences between ICSH and PDPH in terms of atypical presentations. Furthermore, this report aims to identify the criteria for performing an epidural blood patch in patients with ICSH after dural puncture.